Aspectos relevantes sobre a etiofisiopatologia da candidíase vulvovaginal e ação imunomoduladora de β-glucana - Bonfim-Mendonça, Patrícia de Souza (2014)
The high incidence of vulvovaginal candidiasis (VVC), and the clinical relevance of this disease, have been driving research studies to explain the mechanisms of pathogenicity and identification of virulence factors of Candida spp. However, few studies have been targeted in the evaluation of the fungus-host interaction, protective mechanisms involved (modulation of the immune response) or factors associated with susceptibility to infection, particularly in patients with CVVR (recurrent vulvovaginal candidiasis). Therefore, the aim of this study was to evaluate relevant aspects about the etiopathophysiology of vulvovaginal candidiasis and immunomodulatory action of β-glucan. Experimental model used was clinical isolates of C. albicans and C. glabrata originating from women with different symptomatology for VVC: ASS (no symptoms), VVC (one episode) and RVVC (several episodes/year). The summary of our results showed that, the isolated RVVC of the C. albicans caused biochemical changes in the inflammatory response triggered by neutrophils, especially in the production of reactive oxygen and nitrogen species leading to disease susceptibility. On the other hand, isolates of C. glabrata did not show such responses, demonstrating susceptibility to the action of neutrophils. In this context, we note the ability of β-glucan extracted from laminarin digitata in immunomodulate the neutrophil response. β-glucan significantly increased the production of oxidant species, and modulated the release of cytokines, suggesting that this polysaccharide may be a immunomodulatory effective of microbicidal response of the neutrophils. Knowing the different behavior of the clinical isolates of C. albicans, we studied factors related to adherence to human cervical cells (HeLa) and the expression of important genes in this process, eg ALS (agglutinin-like sequence) and SAP (secreted aspartyl proteins). Observed that despite the isolated ASS, have greater adhesion capacity on HeLa cells, a down-regulation genes related with pathogenicity. On the other hand, the VVC and RVVC isolates had lowerest potential for adhesion, but were able to significantly up-regulation important genes in the infection process. Based on these results we can highlight the relationship fungal-host, which occurs mainly in cases of recurrent VVC and suggests β-glucan as an potential immunomodulatory for RVVC response.